Progress towards recalibration of spectrographs - Kallepalli, Akhil; Soori, Umair; James, David; Richardson, Mark A. (IEEE, 2019)
The spectral resolution of a spectrograph depends on the input slit width, the diffraction grating grooves and the number of imaging sensor/detector pixels. Due to the proprietary nature of spectrograph designs, recalibration by end-users can be challenging. Most calibration procedures currently published are applicable to in-house instruments or spectrographs with access to the internal specifications. Narrowing the input slit improves the resolution but also reduces the throughput of the imaging system. We attempted to recalibrate an Offner-based spectrograph by using a larger detector plane (an imaging system with a larger sensor), to vary the distance along the focal plane; and by utilising lens optics. Basic experiments were conducted by varying the distance from the exit window and inserting a lens to magnify the spectrograph output onto the larger detector plane. We concluded that the calibration could not be achieved using simple optics within the scope of our experiments. This article addresses a gap in literature that does not present the research community with the unsuccessful steps that are not applicable to similar problem statements. The alternative would be to rely on reflective optics, but this approach may reduce portability.
Keywords: Offner-based Spectrographs; Optical Equipment; Spectral Domain; Focal Plane Array; Diffraction Gratings